A critical investigation of the sort - term science in-service teacher education programme conducted in three education divisions in Sri Lanka - Leelaratne, S. (My University, 1994)
In this study an attempt is made, to analyse the in-service education needs of the science teachers in relation to day to day classroom teaching, and to assess to what extent the present form of in-service education programme made available for these teachers, is designed in a manner to meet the demand...